Comprehensive Evolutionary Analysis of Lamprey TNFR-Associated Factors (TRAFs) and Receptor-Interacting Protein Kinase (RIPKs) and Insights Into the Functional Characterization of TRAF3/6 and RIPK1 - Hou, Jianqiang; Pang, Yue; Li, Qingwei (Frontiers in Immunology, 2020)
TNFR-associated factors (TRAFs) and receptor-interacting protein kinase (RIPKs) are important immunological linker molecules in the mammals and play important roles in TNFα, TLR and IFN signaling pathways. But their evolutionary origins of vertebrates had previously not been described in lamprey. Here, we searched the genomes of the Lampetra japonicum, Lethenteron reissneri and Petromyzon marinus for genes encoding trafs and ripks and performed homologous sequence alignment, phylogenetic tree, functional domains, conserved motif, gene structure, and synteny analysis to determine their evolutionary relationships. The distribution of the lamprey trafs and ripks family and the immune response of the gene family in lampreys stimulated by different pathogens were also demonstrated, suggesting a role of structural changes in expression and functional diversification. Additionally, the dual luciferase reporter gene assay showed that the addition of exogenous stimulation (TNFα or IFN) to the over expression of LjLRIPK1a or LjTRAF3/6 significantly down-regulated NF-κB or ISRE expression. LjRIPK1a can significantly enhance caspase 8 activity and overexpression of LjRIPK1a or LjTRAF3/6 in HEK293T cells results in cell apoptosis. In summary, this study has important effect on the understanding of the traf and ripk gene family in different vertebrates. Our results also provide new evidence for the evolution of vertebrate TRAFs and RIPKs and the regulation of immune regulation.